PERAN METODE HYPNOTEACHING TERHADAP MINAT BELAJAR PADA MATA PELAJARAN PKN DI SDN 13 KWANDANG, GORONTALO - Rahmawati, Sarlin; Pomalingo, Samsi; Katili, Sukri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The research aims to understand the role of teachers in implementing the hypnoteaching method in the Civics Education (PKn) subject for third and fifth grades at SDN 13 Kwandang. The type of research used is qualitative, and the data collection techniques include observation, interviews, and documentation. The results indicate that the hypnoteaching method at SD Negeri 13 Kwandang plays a significant role in enhancing the learning process, especially in fifth grade. This method combines hypnosis techniques with teaching to create a conducive classroom atmosphere, making students more open and receptive. By using subtle hypnosis techniques, teachers can help students achieve a relaxed state, which enhances memory retention and positive learning experiences. Additionally, hypnoteaching fosters a more harmonious learning environment, allowing students to feel safe to actively participate in discussions. Through this approach, students not only learn academically but also develop emotional well-being and good character. The use of this method contributes to increased interest and motivation among students in the Civics Education (PKn) subject. When teaching is conducted interactively and relevant to everyday life, students tend to be more engaged and enthusiastic about understanding the material. Teachers play the role of facilitators who create a safe and engaging learning atmosphere, encouraging students to express their opinions confidently. With this comprehensive approach, hypnoteaching not only enhances the effectiveness of learning but also helps students become active and responsible citizens. This method demonstrates great potential in supporting a more enjoyable and meaningful learning experience